The Ancient Culture of the Bering Sea and the Eskimo Problem No. 1 - Rudenko, S. I. (Sergeĭ Ivanovich), 1885-1969 (Book collections on Project MUSE., 1961)
Results of archaeological expedition working on Soviet shore of Bering Strait in 1945; theories of origin of Eskimo culture based on these results. Originally published as Drevnaya kul'tura Beringova morya i eskimosskaya problema, Leningrad, 1947.